2017
DOI: 10.1016/j.nut.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Stereology shows that damaged liver recovers after protein refeeding

Abstract: Awareness of these data will add to a better morphologic understanding of malnutrition-induced hepatopathies and will help clinicians improve the diagnosis and treatment of this condition in humans and in veterinary practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Among those, an increase in the demand of aa, as building blocks of proteins, has been described 18 . A recent study showed that protein restriction in mice decreases the volume of both the liver and hepatocytes, and these defects were not completely reversed by aa restoration in the diet 19 . Hence, we can speculate that a deficiency in dietary protein intake could exert a strong and lasting impact on the capacity of recovery in cases of hepatocellular deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Among those, an increase in the demand of aa, as building blocks of proteins, has been described 18 . A recent study showed that protein restriction in mice decreases the volume of both the liver and hepatocytes, and these defects were not completely reversed by aa restoration in the diet 19 . Hence, we can speculate that a deficiency in dietary protein intake could exert a strong and lasting impact on the capacity of recovery in cases of hepatocellular deterioration.…”
Section: Discussionmentioning
confidence: 99%